2013
DOI: 10.1016/j.jpubeco.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Does retiree health insurance encourage early retirement?

Abstract: The strong link between health insurance and employment in the United States may cause workers to delay retirement until they become eligible for Medicare at age 65. However, some employers extend health insurance benefits to their retirees, and individuals who are eligible for such retiree health benefits need not wait until age 65 to retire with group health coverage. We investigate the impact of retiree health insurance on early retirement using employee-level data from 54 diverse firms that are clients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Research on similar programs, e.g. Medicare, COBRA and the Veterans Affairs insurance expansion, provides some indication (Gustman and Steinmeier, 1994; Karoly and Rogowski, 1994; Madrian, 1994; Gruber and Madrian, 1995; Lumstaine, Stock and Wise, 1996; Rust and Phelan, 1997; Blau and Gilleskie, 2001, 2006, 2008; Boyle and Lahey, 2010; Robinson and Clark, 2010; Strumpf, 2010; French and Jones, 2011; Coe et al, 2013; Martin and Woodbury, 2013; Nyce et al, 2013). This literature has generally shown that health insurance availability for retirement-aged individuals induces retirement, though the magnitudes of the effects vary across settings.…”
Section: Introductionmentioning
confidence: 99%
“…Research on similar programs, e.g. Medicare, COBRA and the Veterans Affairs insurance expansion, provides some indication (Gustman and Steinmeier, 1994; Karoly and Rogowski, 1994; Madrian, 1994; Gruber and Madrian, 1995; Lumstaine, Stock and Wise, 1996; Rust and Phelan, 1997; Blau and Gilleskie, 2001, 2006, 2008; Boyle and Lahey, 2010; Robinson and Clark, 2010; Strumpf, 2010; French and Jones, 2011; Coe et al, 2013; Martin and Woodbury, 2013; Nyce et al, 2013). This literature has generally shown that health insurance availability for retirement-aged individuals induces retirement, though the magnitudes of the effects vary across settings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on impacts of retiree health insurance include Blau and Gilleskie (2001 Blau and Gilleskie (2008), Gustman and Steinmeier (1994), French and Jones (2011), Karoly and Rogowski (1994), Robinson and Clark (2010), Madrian (1994), and Nyce et al (2013). …”
mentioning
confidence: 99%
“…A large literature in economics finds that the need for health insurance has induced people to participate in the labor force (Antwi, Moriya, and Simon 2013;Blau and Gilleskie 2001;Buchmueller and Carpenter 2012;Dillender 2015b;Nyce et al 2013;Strumpf 2010). Prior to the ACA, there were few good health insurance options for the near elderly outside of employment.…”
Section: Labor Force Compositionmentioning
confidence: 99%